Molecular epidemiological analysis of Influenza viruses in Influenza-like illness cases: a retrospective study in Chongqing Hi-Tech Zone, China (2021–2024) - Wei Cai; Yuhang Deng; Pan Xu; Jianjiang Xue (Virology Journal)
Abstract Objectives To analyze the molecular epidemiological characteristics of influenza viruses in influenza-like cases in Chongqing Hi-Tech Zone, China, to provide data support and a scientific basis for optimizing influenza prevention and control strategies in the region. Materials and methods A retrospective analysis was conducted on the molecular epidemiological characteristics of influenza viruses in influenza-like cases at a hospital in Chongqing Hi-Tech Zone from 2021 to 2024. Colloidal gold detection of viral antibodies, fluorescent PCR detection of nucleic acids, and gene sequencing were used to identify the different subtypes. Results Among 39,986 ILI specimens tested using the immunocolloid gold method, 6,616 influenza viruses were detected, with a detection rate of 16.54%. Infections included 4,464 influenza A viruses (67.50%), 2,033 influenza B viruses (30.73%), and 119 co-infections of influenza A and B viruses (1.77%).In this region, H3N2 was the predominant subtype of influenza A, and Victoria was the main subtype of influenza B. Conclusion Influenza epidemics in the winter and spring seasons in Chongqing Hi-Tech Zone were predominantly caused by influenza A, with influenza B also circulating. Influenza A strains were mainly H3N2, while influenza B strains were primarily Victoria.